Developing European Key Competences with Green Education - Sacco, Margherita Maria; Vitti, Elena Liliana; Parola, Alberto (European Journal of Sustainable Development, 2020)
Building&Learning Project is action-research focused on the environmental consequences of technology. The didactic design is structured on the classic program proposed for the scholar discipline Technology for the first grade of secondary school; it tries to answer to the requirements of the National Plan for a Digital School (PNSD). Our first aim is to overcome the diktat “teach how to use the media” and reach the capacity to “teach with the media”, to avoid the danger of a “technocentric illusion” and to get the purpose to develop the competences proposed by Europe and Italy. Our teacher-researcher prepared every lesson to help the students to: a) get the disciplinary aim; b) understand the process and the consequences that every technology brings with itself; c) apply the theory in a practice activity. Every lesson is divided in two phases: the theoretical part is based on the method of Cooperative Learning, while the second part is a practice activity where students build with LEGO Education Kit a model that forecasts the application of the theory. After the first period, we introduced also a Story-telling part because the students showed great difficulty in expressing the theory explained. Keywords: European key competences - Media Education – Cooperative Learning – Sustainability education – STEM